Mendelian randomization analysis reveals causal relationship between depression, antidepressants and benign paroxysmal vertigo - Yayun Liao; Kejian Zhou; Zhiyan Guo; Lu Qin; Shan Deng; Hong Yang; Baohui Weng; Liya Pan (Scientific Reports)
Abstract Benign paroxysmal vertigo (BPV) is a common cause of dizziness, and some patients are comorbid with psychiatric disorders such as depression, requiring intervention with antidepressants. However, the causal association between BPV, depression and antidepressants has not been clearly established. We used two-sample bidirectional Mendelian randomization (MR) to analyze the causal association between BPV, depression, and antidepressants. From a Finnish database, 43,280 patients with depression and 329,192 controls, and 106,785 patients with antidepressants and 88,536 controls were selected. Independent single nucleotide polymorphisms (SNPs) for depression and antidepressants were used as instrumental variables (IVs) with genomic significance (p < 5 × 10–8). Similarly, genome-wide association study (GWAS) data for BPV were selected from a Finnish database consisting of 8280 cases and 359,094 controls. Afterwards, a two-sample MR study was performed using R’s Two Sample MR and MR-PRESSO software packages. The multiplicity and heterogeneity of the data, as well as the effect of individual SNPs on the results were investigated. The main statistical analyses were weighted median, weighted mode, MR-Egger and weighted inverse variance weighting (IVW) for random effects. Finally, we identified associations between BPV, antidepressants and depression. Four outliers (rs3773087, rs4619804, rs62099231, rs7192848) were found to be associated with depression. After removing the outliers, the statistics showed no heterogeneity (p > 0.05) and horizontal pleiotropy (p > 0.05). Antidepressants were also found to have a random effect IVW (β = 0.440; p = 9.692 × 10–6; OR = 1.553; 95% CI 1.278–1.887). The inverse MR random effects IVW results showed a causal association between BPV and antidepressants (β = 0.051; p = 0.045; OR = 1.052; 95% CI 1.001–1.1066). In conclusion, there was a significant causal association between antidepressants and BPV at the genetic level. Clinicians should pay attention to patients with BPV combined with depressive disorders and develop timely interventions.